MEMBANGUN LITERASI TAKDIR DI KALANGAN GENERASI MILENIAL : (ANALISIS ISI ATAS KAJIAN USTADZ HANAN ATTAKI DI SAMARINDA) - S. Dinar Annisa Abdullah (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2025)
This study examines how the Islamic missionary message about the concept of destiny is constructed by Ustadz Hanan Attaki in his lecture entitled "The Secret to Changing Destiny: Soulmate, Fortune, Success" at the Sharing Time event in Samarinda, April 27, 2025. Unlike previous studies that tend to understand destiny within a normative and theological framework, this study offers novelty by examining destiny literacy as a psychospiritual aspect of the millennial generation through the perspective of missionary framing. The method used is qualitative with content analysis, utilizing Robert Entman's framing theory. The results show that Ustadz Hanan frames destiny as a dynamic and transformative spiritual space, not a static provision that negates human effort. The novelty of this study lies in revealing the role of missionary framing as a medium for spiritual literacy as well as psychological therapy for the millennial generation in facing identity crises in the digital era. The contribution of this research not only enriches the study of contemporary missionary communication but also provides practical implications for digital missionary strategies that are more contextual, inspiring, and socially impactful.